Black Fungus Complicated with COVID-19 in a Man with Underlying Non-Hodgkin’s Lymphoma - Erni J Nelwan; Rahajeng N Tunjungputri; Retno S Wardani; Retno Wahyuningsih (Acta Medica Indonesiana)
COVID-19 is a disease reported to suppress cellular immunity. This may lead to the development of opportunistic infections, among others black fungus, or mucormycosis. On the other hand, pre-existing defect in immunity may render patients susceptible to both mucormycosis and COVID-19. Mucormycosis is a relatively rare fungal infection with rapid progression unless diagnosed promptly and treated adequately, and urgent surgical and medical intervention is lifesaving. The manifestation of mucormycosis largely depends on the presence of exposure to the pathogen and the existing risk factor of the host. As black fungus is locally invasive, the majority of cases will involve tissue damage with local destruction and contiguous spread to nearby structure. We here with present a case of black fungus complicated with COVID-19 in a man with underlying non-Hodgkin’s lymphoma.